THE CONCEPT OF CHILDREN'S GAMES IN THE CONTEXT OF SOCIOLINGUOCULTUROLOGY - Xusanova Gulasal Shuhratjon qizi (Western European Studies, 2025)
In this article, the term sociolinguoculturology is explained, and information is provided about the fields with which it is interconnected. In addition, scientists who worked in this broad field and their opinions are presented. The fact that children's games are connected with the cultural environment has been shown in the research strategy. Anthropological studies of games are closely related to cultural change, i.e., evolution, diffusion, or survival, and to other aspects of culture, such as child-rearing practices, religion, ritual, recreation, warfare, and ecology. is indicated. Also, in the article games were studied in such ways as antiquarianism, evolutionism, diffusionism, functionalism, structuralism. It should be noted that familiarization and playing of not only folk games, but also other state games of children will help to expand their imagination, at the same time increase their thinking ability, increase their interest in knowing the world
Keywords: sociolinguoculturology; cultural studies; sociolinguistics; cultural traditions